Preparation, validation, and evaluation of an information leaflet for patients undergoing day-care surgeries under general anesthesia at a busy tertiary care hospital - Amit Raja Panigrahi; Sumitra G Bakshi (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: It is essential that patients posted for day-care surgeries are adequately prepared preoperatively. Verbal information alone may not be always effective. This study aimed to prepare, validate, and evaluate the efficacy of a patient information leaflet (PIL) for patients undergoing day-care surgeries under general anesthesia (GA). Material and Methods: After approval from the hospital ethics committee a PIL was prepared in English. Readability and design of the leaflet were checked using standard tests: Flesch readability ease test (FRE), Flesch Kincaid grade level (FKGL), and Baker Able leaflet design (BALD). It was translated into three regional languages. The PIL was tested among patients using a questionnaire. Seventy-nine adult patients posted for elective day-care procedures were included while emergency surgeries were excluded. Patient knowledge pre and post-PIL was compared using paired 't' test. The influence of age, gender, and education level on the usefulness of PIL were analyzed using the Chi-square test and knowledge was compared using ANOVA. Results: The English leaflet had an FRE Score of 63.9 and FKGL of 6.4, which is "standard". The BALD score for all leaflets was 25 ("above standard"). The overall knowledge scores significantly improved from 52.6% (preintervention) to 70.7% (postintervention), P < 0.001. Knowledge improvement was seen with the use of PIL in all four languages. Sixty eight percent of patients strongly recommended the PIL while 31% were willing to recommend it to others. Conclusion: The PILs developed in this study have standard readability, good design and validated for efficacy.